The Relationship Between 99mTc-Pertechnetate Hand Perfusion Scintigraphy and Nailfold Capillaroscopy in Systemic Sclerosis Patients: A Pilot Study - Slavica PAVLOV-DOLIJANOVIC,; Nebojsa PETROVIC,; Nada VUJASINOVIC STUPAR,; Nemanja DAMJANOV,; Goran RADUNOVIC,; Dragan BABIC,; Dragana SOBIC-SARANOVIC,; Vera ARTIKO, (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the possible relationship between 99mTc-pertechnetate hand perfusion scintigraphy (HPS) and nailfold capillaroscopy (NC) in systemic sclerosis (SSc) patients. Patients and methods: The study group consisted of 25 SSc patients (6 males; 19 females; mean age 54.2±9.7 years; range, 32 to 67 years), 18 female patients with primary Raynaud's phenomenon (PRP) (mean age 47.1±9.5 years; range, 34 to 65 years) and 10 healthy individuals (3 males, 7 females; mean age 52.7±12.6 years; range, 37 to 73 years). NC and 99mTc-pertechnetate HPS were performed in all examinees. The capillaroscopic findings were classified as normal or scleroderma pattern ("early", "active", or "late"). The fingers-to-palm ratios were calculated for both blood flow (BF) and blood pool (BP) phases of the 99mTc-pertechnetate HPS. Results: Systemic sclerosis patients showed a significantly lower BP ratio than PRP patients and healthy subjects (p=0.004). No statistically significant difference was observed between the SSc and PRP patients in respect to BF ratio. A gradual decrease of BF and BP with the severity of NC microangiopathy pattern ("early", "active" or "late") was found in SSc patients, while the differences were not statistically significant. Patients with diffuse SSc showed lower BF and higher BP than those with limited SSc, while these differences were without statistical significance. There was no significant correlation between BF or BP values and type of SSc (limited or diffuse) (p=0.77 versus p=0.54, respectively) as well as three microangiopathy patterns (p=0.22 versus p=0.54, respectively). Conclusion: 99mTc-pertechnetate HPS improves the evaluation of vascular damage in SSc patients. There is no direct relationship between NC and 99mTc-pertechnetate HPS; however, the two methods complement each other in the assessment of microcirculation in SSc.